Deskripsi Kemampuan Pemecahan Masalah Matematika Ditinjau dari Tingkat Kecerdasan Logis Matematis Siswa Kelas XI - Nurdin Arsyad; Nasrullah; Satriani Safaruddin (Issues in Mathematics Education (IMED), 2020)
This research is a qualitative research with a descriptive approach that aimed to describe students' mathematical problem solving ability in terms the level of mathematical logical intelligence on sequence and series topic. The subjects in this research were 32 students of class XI MIA. The data collection techniques used in this research were the method of test and interview. The results of the research showed that of the three levels of mathematical logical intelligence, research subjects have similarities, starting at the step of understanding the problem subjects expressed the purpose of the problem with their own language and sentence. Then in devising a problem solving plan subjects make a mathematical model. At the step of carrying out the plan, the subjects determine the variable values needed to find a solution to the problem, and at the end of the problem solving process, subjects looking back the steps used and the results obtained. Meanwhile, from the three levels of mathematical logical intelligence, research subjects have differences, that are at the step of understanding the problem where the information revealed by the subject of KLMT is more complete than the subject of KLMS and KLMR. Meanwhile, at the step of carrying out the plan the subject of KLMT in using problem solving procedure more clear and precise. While, the subject of KLMS was able to complete the completion plan whose answer was finally correct, although the procedure used was incorrect. Then, the subject of KLMR faced an obstacle in solving problems because the procedure used was unclear.